Optimasi Produksi Meubel Menggunakan Metode Simpleks - Oktovianus R. Sikas; Arliyanti Irenen Tae; Faustianus Luan (Journal of Mathematics Theory and Applications, 2023)
Currently there are many emerging independent businesses, such as home industries. Olbetsi Furniture is ahome industry that produces household furniture made of wooden planks such as cabinets, chairs and tables.The purpose of this research is to determine the optimal production using the simplex method and to maximizethe cost advantage in the production of Olbetsi furniture using the simplex method. The method used in thisresearch is descriptive method (case study), namely to find out how to solve problems and calculate theproblems that exist in the Olbetsi furniture business. Data collection techniques used in this study wereinterviews and documentation. The results of this study obtained the maximum profit from the production ofcabinets as much as 6.6667≈7 units, while for the production of chairs and tables it was 0 meaning that it didnot need to be produced, to achieve an optimal profit of IDR 4,100,000.-.